In Silico Analysis of the Biodiversity and Conservation Status of Mitochondrial Cytochrome C Oxidase Subunit 1 (CO1) Gene of Taenia multiceps - Kilinc, Seyma Gunyakti; Celik, Figen; Kesik, Harun Kaya; Simsek, Sami (Springer Int Publ Ag, 2020)
Purpose Taenia multiceps resides in the small intestine of carnivores such as dogs, foxes, woles, jackals, while Coenurus cerebralis which is the larval form usually settle in the central nervous system and spinal cord of intermediate hosts like sheep, cattle and goats. The aim of this study was to analyze the haplotype diversity, genetic variation and population structure of the mt-CO1 gene sequences of sheep isolates of T. multiceps had been submitted to GenBank from different countries. Methods A total of 102 sequences from the mt-CO1 gene fragment belong to T. multiceps sheep isolates were used for bioinformatic analyses. Haplotype analysis, phylogenetic analysis and diversity, neutrality, fixation and gene flow analyses were applied to the sequences. Results As a result, 20 haplotypes together with different multiple nucleotide changes were determined after the sequence analysis. Trimmed fragment length was 337 bp hereby 19 polymorphic areas, 12 of which were parsimony informative, were identified, and any insertion-deletion was found. The number of mutations between major haplotypes and the others range from one to nine. The highest (0.72) genetic differentiation (Fst value) was observed between Turkey and Egypt populations while the lowest (- 0.22) was reported from Greece. These findings are important in terms of showing the diversity of nucleotide variation in T. multiceps sheep isolates. Conclusions This study serves as the basis for future large-scale studies on T. multiceps worldwide epidemiology, bioecology, geographic distribution and population structure.
Keywords: Taenia multiceps; Coenurus cerebralis; mt-CO1; In silico analysis